DEMOGRAPHIC INFLUENCE OF THE MUNDA TRIBE IN NORTHEAST INDIA: A SOCIOECONOMIC AND POLITICAL PROFILE IN TRIPURA - Parkash, Dr. Shri (Journal of Current Research and Review (JCRR), 2022)
This research paper aims to investigate the demographic influence of the Munda tribe in Northeast India, with a focus on their socioeconomic and political profile in Tripura. The Mundas have been an integral part of Tripura’s economy for over a century, mainly working in tea gardens and settling in north Tripura. However, no significant work has studied the social, economic, and political existence of the Mundas in Tripura, nor is there a socioeconomic and political profile of the Mundas in Tripura. This research attempts to fill this gap by analyzing the shifting socioeconomic and political status of the Mundas in Tripura. The study will use both qualitative and quantitative methods to analyze the data collected from primary and secondary sources. The research findings will reveal the history and present of the Munda community in Tripura and will be valuable for people who deal with social issues and the government to help the Munda community